Resíduo sólido orgânico urbano e níveis de irrigação no cultivo de crambe - Franco, Claudenir Facincani [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The organic urban solid waste (OUSW) are produced in large amounts causing environmental problems for the population. The agricultural use of this waste can help minimize this impact. Moreover, the water main and limiting factor of production has become an increasingly valued. The crambe can be used in crop rotation and has high value industrial oil and can be used in the manufacture of biofuel and a variety of inputs. Thus, the main of this work was to study the effect of composted OUSW and irrigation levels on growth and grain yield of crambe plants. The experiment was conducted in a greenhouse using soil in PVC containers with dimensions of 0.45 m in height and 0.30 m in diameter. The experimental design was completely randomized in a factorial design (5x4) with three replications. The factors consisted of five doses of composted OUSW corresponding to 0, 15, 30, 60 and 120 Mg ha-1 and four irrigation levels 40, 70, 100 and 130% of the blade calculated based on the method of estimating evapotranspiration (TE) estimated by atmometer. Each replicate contained seven plants. The plants were evaluated for shoot height and diameter and divided into grains, roots, stems and leaves and the plant material was dried in an oven with forced air circulation, temperature 65-70°C until constant weight. Grains were separated 100 units to determine the mass of 100 grains. Based on the results for the various characteristics studied were carried out analyses of variance (F test), for comparison between the doses of residue and levels of irrigation applied, and regression analysis. The composted of OUSW promoted in soil an increase in the values of Active Acidity (pH), Organic Matter (OM), Phosphorus (P), Potassium (K), Calcium (Ca), Magnesium (Mg), Sum of Bases (SB), Capacity Cation Exchange (T), and Bases for Saturation (V%), and reducing the amount of potential acidity (H + Al) soil, and plants of crambe ...

Os resíduos sólidos orgânicos urbanos (RSOU) são produzidos em grandes quantidades causando problemas ambientais para a população. O uso agrícola destes resíduos pode ajudar a minimizar este problema. Além disso, a água fator principal e limitante de produção tem se tornado um bem cada vez mais valorizado. O crambe pode ser usado em rotação de culturas e possui um óleo de alto valor industrial podendo ser utilizado na fabricação de biocombustível e insumos diversos. Assim, o objetivo do trabalho foi estudar o efeito de RSOU compostado e níveis de irrigação no crescimento e na produção de grãos de crambe. O experimento foi conduzido em ambiente protegido, utilizando solo em recipientes de PVC com dimensões de 0,45 m de altura e 0,30 m de diâmetro. O delineamento experimental foi o inteiramente casualizado num esquema fatorial (5x4), com três repetições. Os fatores consistiram de: cinco doses de RSOU compostado correspondentes a 0; 15; 30; 60 e 120 Mg ha-1 e quatro níveis de irrigação 40; 70; 100 e 130% da lâmina calculada com base no método de estimativa da evapotranspiração (ET) estimada pelo atmômetro. Cada repetição continha 7 plantas. As plantas foram avaliadas em altura da parte aérea e diâmetro do colo, e divididas em grãos, raízes, caule e folhas e o material vegetal foi seco em estufa com circulação forçada de ar, à temperatura de 65 a 70ºC, até atingir massa constante. Dos grãos foram separadas 100 unidades para determinação da massa de 100 grãos. Com base nos resultados para as diversas características estudadas foram realizadas análises de variância (teste F), para comparação entre as doses de resíduo e os níveis de irrigação aplicados, e à análise de regressão. O RSOU compostado no solo promoveu aumento nos valores da Acidez Ativa (pH), Matéria Orgânica (MO), Fósforo (P), Potássio (K), Cálcio (Ca), Magnésio (Mg), Soma ...
Keywords: Água; Composto orgânico; Irrigação agricola; Resíduo sólido; Plantas; Crescimento (Plantas); Evapotranspiração; Irrigation